Analysis of the Effectiveness of Pantene Bye #RAMBUTCAPEK Ads with the AISAS Method - Amartiwi, Yasinta; Tomy, Chairian (Universitas Indonesia Mandiri, 2025)
Advertising on Pantene shampoo uses Youtube social media as a promotional medium. The phenomenon that occurred, based on data on the number of viewers on Pantene Bye #RambutCapek advertisements, increased by 22,955,186 million in less than a month at the beginning of the yearِ 2022.ِ Thisِ researchِ is entitledِ